2017
DOI: 10.1016/j.jams.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Local Anesthesia and Two-Point Acupressure on the Severity of Venipuncture Pain Among Hospitalized 6–12-Year-Old Children

Abstract: The aim of the present study was to compare the effects of topical anesthesia and acupressure at the Yintang (Extra 1) and the Laogong (P-8) points on the severity of venipuncture pain among hospitalized 6-12-year-old children. A sample (n = 120) of 6-12-year-old hospitalized children was recruited from two teaching hospitals located in Rafsanjan, Iran. The children were allocated to the topical anesthesia, acupressure, and control groups. For children in the topical anesthesia and the acupressure groups, eute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…In this study, the effects of massage therapy on changes in the physiological parameters induced by intravenous line insertion (including increased respiratory rate, heart rate, and blood pressure, and decreased arterial blood saturation) were investigated in children aged three to six years. The results indicated that the respiratory rate and heart rate of children in both experimental and control groups were significantly higher after IV insertion than before this administration, which is consistent with previous reports (6,7,22,23).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the effects of massage therapy on changes in the physiological parameters induced by intravenous line insertion (including increased respiratory rate, heart rate, and blood pressure, and decreased arterial blood saturation) were investigated in children aged three to six years. The results indicated that the respiratory rate and heart rate of children in both experimental and control groups were significantly higher after IV insertion than before this administration, which is consistent with previous reports (6,7,22,23).…”
Section: Discussionsupporting
confidence: 91%
“…One of the most painful experiences that a child has when admitted to the hospital is inserting the needle into the vein (7,8). For this reason, some researchers have recently focused on studying possible methods of managing and reducing the physiological effects of needle insertion in children (9).…”
Section: Introductionmentioning
confidence: 99%
“… 14 Pour et al., 2017 6–12 year old 120 Venipuncture pain Three-arm RCT Acupressure at the Extra −1 (Yintang) and the PC8 (Laogong) was as effective as topical anesthesia cream in alleviating children's venipuncture pain. 15 …”
Section: Resultsmentioning
confidence: 99%
“…This report evaluates research in pediatric acupuncture and pain management, in which approximately 55% of the selected articles were related to procedural pediatric pain management. The pediatric procedures included infant heel lancing, 3 , 4 , 7 , 8 , 9 ,nsillectomy 10 , 11 and dental-related, 12 myringotomy tube surgery, 13 kidney biopsy, 14 ventipuncture, 15 and endoscopic pre-procedural anxiety. 16 Collectively, these studies researched how acupuncture could lead to the reduction of post-operative pain, emergence irritation, procedural time, and infantile crying.…”
Section: Discussionmentioning
confidence: 99%
“…(72,73) Çocuğun ağrısını azaltmaya yönelik kullanılan farmakolojik olmayan yöntemlerle ilgili yapılan bazı araştırma sonuçları Tablo 1'de gösterildi. (19,25,26,39,40,(44)(45)(46)(47)(48)(49)(50)52,(54)(55)(56)(57)(58)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) Çocuğun anksiyetesini azaltma: Anksiyete, çocuğun hastaneye yatmaya, hastalığa ya da tıbbi işlemlere uyum sağlamasını olumsuz olarak etkiler. (3)(4)(5)7,74) Tıbbi işlemler öncesi stres yaşayan çocuklar sonraki uygulamalarda daha yoğun anksiyete yaşayabilir.…”
Section: Atravmatik Bakım Uygulamalarıunclassified